Pengaruh Karakteristik Individu dan Faktor-Faktor Pekerjaan terhadap Motivasi - Djoko Sunarto; Yeni Kuntari (STIE Widya Manggala, 2013)
This study aimed to determine the effect of individual characteristics and work factors on motivation of Auditors at Public Accounting firms in Semarang period 2012. The sample was 118 auditors. From 118 questionnaires distributed, only 42 questionnaires were returned and analyzed. The analytical tool used in this research was multiple linear regression. The results showed that there was influence between individual characteristics and work factors on motivation. The coefficient of determination of both the independent Variabels of 84.70% means that the variation of these two Variabels in explaining the motivation for the remaining was explained by other Variabels that were not mentioned in the study.